The immunomodulatory potentials of interleukin‐27 in airway allergies. (5th September 2020) - Jafarzadeh, Abdollah; Nemati, Maryam; Jafarzadeh, Sara; Chauhan, Prashant; Saha, Bhaskar
Abstract: Allergic airway disorders such as asthma and allergic rhinitis are mainly caused by inhaled allergen‐induced improper activation and responses of immune and non‐immune cells. One important response is the production of IL‐27 by macrophages and dendritic cells (DCs) during the early stage of airway allergies. IL‐27 exerts powerful modulatory influences on the cells of innate immunity [eg neutrophils, eosinophils, mast cells, monocytes, macrophages, dendritic cells (DCs), innate lymphoid cells (ILCs), natural killer (NK) cells and NKT cells)] and adaptive immunity (eg Th1, Th2, Th9, Th17, regulatory T, CD8 + cytotoxic T and B cells). The IL‐27‐mediated signalling pathways may be modulated to attenuate asthma and allergic rhinitis. In this review, a comprehensive discussion concerning the roles carried out by IL‐27 in asthma and allergic rhinitis was provided, while evidences are presented favouring the use of IL‐27 in the treatment of airway allergies.